Implementasi E-Commerce Menggunakan CMS WordPress Pada UMK Organik Hebat - Ratih; Diana Sukma, Ajeng (Jurnal Teknologi dan Bisnis, 2021)
The development of technology is currently experiencing rapid progress and has an impact on the business world even in everyday life. One of the uses of the internet is as a means of product marketing. Marketing is important for business owners, especially in small businesses or commonly referred to as UMK (Micro Small Business). UMK Organik Hebat is a UMK that produces organic fertilizer and sells plantation tree seeds. Currently, the business processes at UMK Organik Hebat are still using a manual system. Buyers come directly to sellers to make transactions. Product promotion is also still traditional by word of mouth. So far, the obstacles experienced include the lack of marketing and the absence of reports that can be printed through the system so that the owners of UMK Organik Hebat only keep sales records which are then recapitulated in the general ledger. This study aims to implement CMS Wordpress to help promote as well as facilitate the preparation of business reports to increase sales by creating an E-Commerce website that implements CMS WordPress and WooCommerce plugins and My SQL as a database management system so that business actors can manage their business more effectively. and efficient. The data collection method used in this research is literature study, observation and interviews. As for the system development method using the waterfall method. Research results from e-commerce implementation using WordPress CMS and WooCommerce plugins at UMK Organik Hebat can be used to create online stores and help promote product marketing as well as manage business reports